ACOMPANHAMENTO DE PACIENTES COM NUTRIÇÃO ENTERAL EM UM HOSPITAL: UM RELATO DE EXPERIÊNCIA - Pettenon, Marinez K.; Prates, Vanise A. C.; Cassarotti, Betina S.; Huth, Adriane; Rosanelli, Cleci L. S. P.; Piasetzki, Cláudia T. d. R. (Salão do Conhecimento, 2013)
Resumo